Pengaruh Naungan pada Pertumbuhan dan Hasil Bawang Putih (Allium sativum L.) dalam Budidaya Terapung di Ekosistem Rawa - Lili Aisyah; Benyamin Lakitan; Fitra Gustiar (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Domestic garlic demand in Indonesia is still not met by production, especially since garlic is usually only grown in the highlands. This study was conducted to determine the growth and yield of three garlic varieties (Lumbu Kuning, Super Putih, and Sanur) in conditions without shade and with 50% shade using a floating cultivation system in tropical swamp ecosystems. The results showed that the growth and yield of garlic plants that grew without shade were much higher than plants grown under 50% shade. The percentage of germination in Lumbu Kuning without shade is 94%, but shade lowers the percentage to 78%. Significant reductions in vegetative growth parameters such as leaf count, leaf length, pseudo-stem length, and stem diameter were observed as a result of shade treatment. However, the shadow had no significant effect on the weight of fresh and dried roots. Of the varieties tested, floating cultivation conditions are the most favorable for Yellow Lumbu in terms of adaptability and productivity. These results suggest that floating cultivation can support garlic production in tropical swamp ecosystems, while 50% shade is not recommended as it reduces tuber growth and yield.